2021
DOI: 10.1101/2021.03.12.434875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ensemble Switching Unveils a Kinetic Rheostat Mechanism of the Eukaryotic Thiamine Pyrophosphate Riboswitch

Abstract: Thiamine pyrophosphate (TPP) riboswitches regulate thiamine metabolism by inhibiting the translation of enzymes essential to thiamine synthesis pathways upon binding to thiamine pyrophosphate in cells across all domains of life. Recent work on the Arabidopsis thaliana TPP riboswitch suggests a multi-step TPP binding process involving multiple riboswitch conformational ensembles and that Mg2+ dependence underlies the mechanism of TPP recognition and subsequent transition to the translation-inhibiting state of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Similar workflows resolved the structural dynamics in enzymes, 36 the dynamic heterogeneity in multi-domain proteins, 18 and other intrinsically disordered proteins, 37 , 38 and has been used for determining the ensemble switching mechanism of eukaryotic thiamin riboswitch. 39 Furthermore, the integrative structural modeling using DMD and label-based experiments can solve the remaining challenges in highly dynamic systems such as IDPs, IDRs, and complex supertertiary structural dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Similar workflows resolved the structural dynamics in enzymes, 36 the dynamic heterogeneity in multi-domain proteins, 18 and other intrinsically disordered proteins, 37 , 38 and has been used for determining the ensemble switching mechanism of eukaryotic thiamin riboswitch. 39 Furthermore, the integrative structural modeling using DMD and label-based experiments can solve the remaining challenges in highly dynamic systems such as IDPs, IDRs, and complex supertertiary structural dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we showed that TPP AD populates intermediates when its folding is induced by Mg 2+ in agreement with the experiments. 12 We found that at physiological [Mg 2+ ] (≈ 4 mM), AD populated a closed-arm Y-shaped and a holo-form like folded conformations. The holo-form like conformation is not the global minimum in the FES at around physiological [Mg 2+ ] but becomes the global minimum in higher [Mg 2+ ] (≥ 5 mM) even in the absence of the TPP ligand.…”
Section: Discussionmentioning
confidence: 72%
“…44,45 Experiments studying TPP AD folding also suggest that multiple structural ensembles are populated depending on [Mg 2+ ] and TPP-ligand. 12 Further, the timescales associated with the transitions among these ensembles varied from µs to s, indicating significant variations in the barrier heights separating the basins.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation